2017
DOI: 10.1128/jvi.01759-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging with Bioluminescent Enterovirus 71 Allows for Real-Time Visualization of Tissue Tropism and Viral Spread

Abstract: Hand, foot, and mouth disease (HFMD) is a reemerging illness caused by a variety of enteroviruses. The main causative agents are enterovirus 71 (EV71), coxsackievirus A16 (CVA16), and, most recently, coxsackievirus A6 (CVA6). Enterovirus infections can vary from asymptomatic infections to those with a mild fever and blisters on infected individuals' hands, feet, and throats to infections with severe neurological complications. Viral persistence for weeks postinfection (wpi) has also been documented by the demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…We found no significant differences when we measured the total ventral bioluminescence intensity ( S1B Fig ). Based on our experimental observations, and previous reports [ 33 , 34 ] describing the successful delivery of furimazine in the peritoneal cavity, the i. p. route was the method of choice in all subsequent experiments.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…We found no significant differences when we measured the total ventral bioluminescence intensity ( S1B Fig ). Based on our experimental observations, and previous reports [ 33 , 34 ] describing the successful delivery of furimazine in the peritoneal cavity, the i. p. route was the method of choice in all subsequent experiments.…”
Section: Resultsmentioning
confidence: 78%
“…Nanoluciferase is a relatively new luciferase compared to the widely used firefly, Renilla or Gaussia luciferases and its application for in vivo imaging remains to be fully investigated [ 24 , 28 ]. To date, NLuc and its furimazine substrate have been effectively employed as bioluminescence system to study spread and tissue tropism of pathogens in real time imaging [ 23 , 34 , 42 , 43 ] with light signal outputs greater than that of Gaussia and firefly luciferases [ 30 ]. However, the use of NLuc to track T .…”
Section: Discussionmentioning
confidence: 99%
“…The CNS is relatively inaccessible to immune surveillance compared with other tissues, which makes it particularly vulnerable to persistent infection. Using in vivo imaging, a recent study has demonstrated that EV-A71 infection of AG129 mice, in which alpha/beta and gamma interferon receptors are deficient, shows rapid spread and long-term persistence of the virus in the brain of surviving animals (Caine and Osorio, 2017). Interestingly, high viral loads are maintained in the brain even at 6 weeks following infection, whereas viral loads in other tissues including heart, lung, liver, spleen and intestine are gradually reduced to a lower level.…”
Section: Persistent Infectionmentioning
confidence: 99%
“…The establishment of viral reverse genetics and reporter viruses has greatly facilitated the development of animal models as tools for the evaluation of candidate vaccines and therapeutic drugs. So far, luciferase-expressing recombinant viruses have been well demonstrated for herpes simplex virus [ 29 , 30 ], enterovirus 71 [ 31 ], Japanese encephalitis virus [ 32 ], and Sendai virus [ 33 ], as well as for IAV [ 1 , 16 , 24 ]. Infection of these viruses allows for real-time monitoring in virus replication and dissemination in living animals by noninvasive in vivo imaging [ 34 ], facilitating the evaluation of candidate vaccines and therapeutic antibodies.…”
Section: Discussionmentioning
confidence: 99%